Genome‐wide association analysis of dementia and its clinical endophenotypes reveal novel loci associated with Alzheimer's disease and three causality networks: The GR@ACE project. Issue 10 (28th August 2019) - Moreno‐Grau, Sonia; de Rojas, Itziar; Hernández, Isabel; Quintela, Inés; Montrreal, Laura; Alegret, Montserrat; Hernández‐Olasagarre, Begoña; Madrid, Laura; González‐Perez, Antonio; Maroñas, Olalla; Rosende‐Roca, Maitée; Mauleón, Ana; et al.
Abstract: Introduction: Large variability among Alzheimer's disease (AD) cases might impact genetic discoveries and complicate dissection of underlying biological pathways. Methods: Genome Research at Fundacio ACE (GR@ACE) is a genome‐wide study of dementia and its clinical endophenotypes, defined based on AD's clinical certainty and vascular burden. We assessed the impact of known AD loci across endophenotypes to generate loci categories. We incorporated gene coexpression data and conducted pathway analysis per category. Finally, to evaluate the effect of heterogeneity in genetic studies, GR@ACE series were meta‐analyzed with additional genome‐wide association study data sets. Results: We classified known AD loci into three categories, which might reflect the disease clinical heterogeneity. Vascular processes were only detected as a causal mechanism in probable AD. The meta‐analysis strategy revealed the ANKRD31 ‐rs4704171 and NDUFAF6 ‐rs10098778 and confirmed SCIMP ‐rs7225151 and CD33 ‐rs3865444. Discussion: The regulation of vasculature is a prominent causal component of probable AD. GR@ACE meta‐analysis revealed novel AD genetic signals, strongly driven by the presence of clinical heterogeneity in the AD series. Highlights: We detected three gene categories operating differently in AD subgroups of patients. Vasculature regulation may be an essential part of the causative mechanism in pure AD. Two novel signals reached genome‐wide significance in ANKRD31 and NDUFAF6 loci. We confirmed SCIMP‐rs7225151 and CD33‐rs3865444 to be genome‐wide significant. Genetic discoveries are strongly impacted by the presence of subgroups of AD.